Automatic Chicken Egg Hatching Using The Fuzzy Logic Control Method In An Effort To Increase Hatching Rates - Widy Seftiawan; A.Rahman; Muhammad Amri Yahya (International Journal of Health Engineering and Technology, 2026)
The process of hatching chicken eggs requires stable temperature and humidity control for optimal embryo development. This study aims to design and implement an automatic chicken egg hatching system based on Fuzzy Logic Control to control the temperature and humidity of the incubator adaptively. The study uses a design method with the Mamdani Fuzzy Logic approach. The object of the study is an automatic chicken egg hatching system, while the research sample is data from temperature and humidity sensor readings and actuator responses during the testing process. The research instruments consist of a DHT22 sensor, an ESP8266 microcontroller, a relay module, a heating lamp, a fan, a roller motor, an irrigation system, and a 16x2 LCD. Data analysis is carried out through functional testing of the system and evaluation of temperature and humidity control capabilities based on fuzzy inference results. The results of the study showed that the system was able to maintain the temperature in the range of 37.5–37.7°C with an average of 37.6°C and humidity in the range of 51.1–51.7% RH with an average of 51.44% RH, and run the actuator automatically according to the rules of Fuzzy Logic Mamdani. It was concluded that the system was able to maintain the stability of the incubator conditions so as to support the process of hatching chicken eggs automatically and adaptively.